Digitalisasi Desa dalam Meningkatkan Efektivitas Pelayanan Publik di Desa Sungai Baung Kecamatan Pengabuan Kabupaten Tanjung Jabung Barat - Ovie Yanti; Derma S. Gultom; Candra Irawan; Siti Zaadah; Erika Saputri; Edi Purwanto (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
Village digitalization is one of the village government transformation strategies in providing fast, transparent, and easily accessible services to the community. Through the use of village websites, village governments strive to accelerate administrative processes, disseminate public information, and strengthen community participation. The methods used in this community service activity are participatory and collaborative. The results of the activity evaluation show that the implementation of digitalization in Sungai Baung Village has had a positive impact on the efficiency of service time, increased access to information, and community involvement in village development. However, challenges such as limited human resources, internet infrastructure, and community digital literacy are still obstacles that need to be overcome. Therefore, ongoing efforts are needed in training and mentoring, provision of digital facilities, and collaboration between parties to ensure the success of village digitalization as a whole.